The Existence of Rossy's Entertainment Studio in Modeling Talent Development Education - Novianti Ariantini; Alis Triena Permanasari; Dadang Dwi Septiyan (CV. Edujavare Publishing, 2026)
The studio functions as a non-formal educational institution that facilitates participants in developing technical modeling skills including catwalk technique, posing, facial expression, as well as soft skills encompassing self-confidence, creativity, discipline, and character. This research employs a descriptive qualitative approach. Data were collected through participatory observation, in-depth semi-structured interviews, and documentation. Research subjects include the studio owner, two professional trainers, twelve active participants, and eight parents. Data analysis followed the Miles, Huberman, and Saldana interactive model comprising data reduction, data display, and conclusion drawing, with credibility ensured through source and method triangulation. Findings reveal that Rossy's Entertainment Studio, established in 2015, has grown from 15 to over 80 active participants and has accumulated numerous achievements at regional and national levels. The studio offers comprehensive training programs covering catwalk fundamentals, posing techniques, fashion knowledge, public speaking, and character education. Its existence significantly contributes to participants' talent development through a professional coaching team, a collaborative and supportive learning environment, and regular participation in fashion shows and competitions. Parental support and professional trainers are identified as primary supporting factors, while self-consciousness in new participants, academic time constraints, program costs, and limited physical facilities constitute the main inhibiting factors. The study concludes that Rossy's Entertainment Studio plays a pivotal role in nurturing modeling talent and building participants' positive character, positioning itself as a meaningful non-formal education provider in Serang City.